CONSUMER BEHAVIOR TOWARDS NEW FINANCIAL TECHNOLOGIES: AN ANALYSIS OF THE ADOPTION OF DIGITAL BANKING SERVICES - NIOATA (CHIREAC) ROXANA-MIHAELA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This paper examines the determinants of digital banking adoption in light of rapidly evolving technologies and their impact on consumers' financial behavior. The study explores how risk perception, trust in digital security, familiarity with technology and convenience preferences influence the decision to use online or mobile banking solutions. Also discussed are relevant theoretical models, such as the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Technology Acceptance Model (TAM), which help to explain the factors that influence adoption intentions of new financial technologies.